(3aj GdHWGbI YbGFO GdRjOjIs - (3eLghds ((3YGeQ Hf YHO Gddg Hf YHjI GdQMHjs)
(3ChdgG (B:s
.. (3hGYde Cf GdcdGe EfeG gh aj GdCLSGe CdajJgG hCeG JQGcHgG adG NdGa aj MOhK cKjQ efgG cGdLhGH(B...s
(3BNQgG (B:s
(3MjK eG CQOJ UdGI Gf Jchf dc QVG hdMbg (B.. (3jG CcQe GdCcQejf jG CQMe GdQGMejf hBNQ OYhGfG Cf GdMeO ddg QH GdYGdejfs
(3HBNQgG hQbGJ aj CSeGA Gddg GdMSfis
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3GdJedcGJ h GdhbajGJ (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds